Application of the Storytelling Method to Improve Early Childhood Language Development at Islamic Kindergarten Al Ittifaqiah Indralaya - Agustini, Tri; Fitriani, Yessi; Effendi, Darwin (Journal of Social Work and Science Education, 2023)
Classroom Action Research is one of the efforts that can be taken by teachers/researchers to test the effectiveness of a learning method and measure students' abilities in their treatment in a research class. Based on the low language skills of students in the Ittifaqiah Indralaya Islamic Kindergarten students, where in initial observations only 25% of my students had fairly good language skills, the researcher then conducted PTK using the storytelling method. The research was carried out for two cycles in which two actions were carried out in each cycle. Based on the results of the first action of cycle I, an increase of 60% was achieved, which was then followed by the second action of cycle I, which achieved an increase of 85%. In the first action cycle II, the research target of 90% was exceeded to 95% or leaving 1 student who had not reached the specified KKM. Based on the data analysis, it can be concluded that the storytelling method is successful in improving the language skills of Ittifaqiah Indralaya Islamic Kindergarten students.